Male-Female:: Destabilizing Binary Opposition in Detective Conan the Series - Chaithanaphat, Sutasinee (Journal of Letters, 2025)
This article presents a study of Japanese detective fiction that has been adapted into the Thai-dubbed television cartoon series Detective Conan the Series from TIGA Company, with this study focusing only during Years 1–5. This article highlights the destabilizing of the binary oppositions, with the study exploring the male-female binary opposition, which reveals the possibility of subordinate power challenging and destabilizing another. The reversal of roles reflects the ability to negotiate with the dominant power. Despite this, women have the ability to challenge male power; however, in their efforts to do so and their given roles, women are eradicated from society by the male protagonists. Consequently, it is indisputable that men still hold authority over women